Facilitators and barriers of change toward an elder-friendly surgical environment: perspectives of clinician stakeholder groups - Heather M. Hanson; Lindsey Warkentin; Roxanne Wilson; Navtej Sandhu; Susan E. Slaughter; Rachel G. Khadaroo (BMC, 2017)
Abstract Background Current acute care surgical practices do not focus on the unique needs of older adults. Adverse outcomes in older patients result from a complex interrelationship between baseline vulnerability and insults experienced during hospitalization. The purpose of this study is to assess the organizational readiness and the barriers and facilitators for the implementation of elder-friendly interventions in the acute care of unplanned abdominal surgery patients. Methods This cross-sectional mixed methods study included a convenience sample of clinician stakeholder groups. Eight focus groups were conducted with 33 surgical team members including: 10 health care aides, 6 licensed practical nurses, 6 registered nurses, 4 nurse managers and 7 surgeons, to identify barriers and facilitators to the implementation of an elder-friendly surgical unit. Audio recordings of the focus groups were transcribed verbatim and analysed using interpretive description techniques. Transcripts were coded along with explanatory memos to generate a detailed description of participant experiences. Themes were identified followed by refining the codes. Participants also completed the Organizational Readiness for Implementing Change questionnaire. Differences in organizational readiness scores across clinician stakeholder groups were assessed using Kruskal-Wallice tests. Mann-Whitney tests (Bonferroni's corrections for multiple comparisons) were conducted to assess pair-wise relationships. Results The focus group data were conceptualized to represent facilitators and barriers to change at two levels of care delivery. Readiness to change at the organizational level was evident in five categories that reflected the barriers and facilitators to implementing an elder-friendly surgical unit. These included education, environment, staffing, policies and other research projects. At the individual level barriers and facilitators were apparent in staff members' acceptance of new roles and duties with other staff, family and patients. Examples of these included communication, teamwork and leadership. The mean change commitment and change efficacy scores on the Organizational Readiness for Implementing Change Questionnaire were 3.7 (0.8) and 3.5 (0.9) respectively. No statistically significant differences were detected between the stakeholder groups. Conclusions Staff are interested in contributing to improved care for elderly surgical patients; however, opportunities were identified to enhance facilitators and reduce barriers in advance of implementing the elder-friendly surgical unit intervention.